JUSTIFICATION OF THE EFFECTIVENESS OF CIRCUIT TRAINING IN COMBAT SAMBO FOR 19–20-YEAR-OLD CADETS - Ruslanbek Azatovich Matchanov (Innovate Conferences, 2025)
This thesis provides a theoretical justification for the effectiveness of circuit training in the physical preparation of 19–20-year-old cadets practicing combat sambo. It reviews literature on high-intensity circuit training and its impacts on combat athletes’ fitness, endurance, and performance. The analysis highlights that circuit training – characterized by successive exercise stations with minimal rest – can significantly improve both general and special physical preparedness in young adult sambo practitioners. Emphasis is placed on how circuit training increases training density, enhances strength and aerobic endurance simultaneously, and mirrors the high-intensity demands of combat sambo competition. The findings from sports science studies (including cross-disciplinary research on CrossFit-style training) are discussed to substantiate the efficacy of circuit regimens. Results indicate that cadets engaging in well-designed circuit training experience improved cardiovascular fitness, muscular endurance, and faster recovery, which collectively enhance combat performance. The thesis concludes by recommending circuit training as an efficient and evidence-based method for optimizing physical conditioning in combat sambo, while also noting best practices for implementation in a cadet training context.
Keywords: combat sambo; circuit training; high-intensity training; physical fitness; endurance; cadets; combat sports conditioning